2023
DOI: 10.1021/acs.jpcc.3c02601
|View full text |Cite
|
Sign up to set email alerts
|

Operando Raman Spectroscopy for Evaluating Concentration Changes in Li- and Na-Based Solid Polymer Electrolytes

Abstract: The solid polymer electrolytes (SPEs) can apply to all-solid-sate batteries using various cations as the carrier species. Herein, we performed operando Raman spectroscopy to evaluate the concentration changes with ionic transport in the Li- and Na-based SPEs composed of ether-based host polymer and MN­(SO2CF3)2 (M = Li, Na; MTFSA), with the aim of extracting differences in behavior under electrochemical operation. In the [Li | Li-based SPE | Cu] cell, the integrated intensities of TFSA anions changed near the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…While these effects can be detrimental to ion conduction, the polymer can facilitate conduction through its segmental motion and above the glass transition temperature. ,, These factors can be studied using Raman spectroscopy from the chemical and structural changes of the molecules. Raman spectroscopy has been used to determine the crystallinity of polymer and salt, , to analyze their solvation shell structure/complexation, , to perform operando analysis to detect changes in ion concentration as well as to monitor the electrode/electrolyte interface . To correlate the properties of the polymer electrolyte with the behavior in electrochemical cells in real time, mock cells with transparent glass covers have been employed for use in Raman spectroscopic characterizations under the same conditions. , …”
Section: Introductionmentioning
confidence: 99%
“…While these effects can be detrimental to ion conduction, the polymer can facilitate conduction through its segmental motion and above the glass transition temperature. ,, These factors can be studied using Raman spectroscopy from the chemical and structural changes of the molecules. Raman spectroscopy has been used to determine the crystallinity of polymer and salt, , to analyze their solvation shell structure/complexation, , to perform operando analysis to detect changes in ion concentration as well as to monitor the electrode/electrolyte interface . To correlate the properties of the polymer electrolyte with the behavior in electrochemical cells in real time, mock cells with transparent glass covers have been employed for use in Raman spectroscopic characterizations under the same conditions. , …”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, in-situ Raman spectroscopy was employed to investigate the behavior of batteries using Li and Na electrolytes. 31 By utilizing the relationship between concentration changes and peak shifts in the Raman spectra, the diffusion properties of Na + and Li + were compared in solid polymer electrolytes, which revealed that solvation/desolvation of Na + by TFSA ¹ (TFSA = bis(trifluoromethylsulfonyl)amide) during ionic transport is more difficult than the case of Li + .…”
Section: Introductionmentioning
confidence: 99%
“…To enhance safety, there has been increasing interest in all-solidstate batteries that leverage non-ammable and non-volatile solid electrolytes, such as sulde, oxide, and organic polymer materials, as alternatives to organic liquid electrolytes. [10][11][12][13][14][15][16][17] In addition, all-solid-state batteries can be stacked within a single external package without the risk of liquid short-circuiting. This approach is effective for improving both energy density and safety properties.…”
Section: Introductionmentioning
confidence: 99%